2021
DOI: 10.1167/tvst.10.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Anterior Segment Optical Coherence Tomography to Predict the Presence of Plateau Iris

Abstract: The purpose of this study was to evaluate the diagnostic performance of deep learning (DL) anterior segment optical coherence tomography (AS-OCT) as a plateau iris prediction model. Design:We used a cross-sectional study of the development and validation of the DL system. Methods:We conducted a collaboration between a referral eye center and an informative technology department. The study enrolled 179 eyes from 142 patients with primary angle closure disease (PACD). All patients had remaining appositional angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Kumar et al reported the prevalence of plateau iris at 30% in PACS and PACG in South-East Asian patients,17 18 while in a study in Japan, it was found in 20% of cases of PAC and PACG 21. In Indian patients, plateau iris was found in 31.7% of PACG,22 whereas in our previous report, it was found in 47.5% of PACD cases 15. The accuracy of manual grading of AS-OCT was relatively low, however, at 51%–65%, indicating a discrepancy between AS-OCT and UBM, the latter being the reference standard for PIC classification in the literature.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Kumar et al reported the prevalence of plateau iris at 30% in PACS and PACG in South-East Asian patients,17 18 while in a study in Japan, it was found in 20% of cases of PAC and PACG 21. In Indian patients, plateau iris was found in 31.7% of PACG,22 whereas in our previous report, it was found in 47.5% of PACD cases 15. The accuracy of manual grading of AS-OCT was relatively low, however, at 51%–65%, indicating a discrepancy between AS-OCT and UBM, the latter being the reference standard for PIC classification in the literature.…”
Section: Discussionmentioning
confidence: 64%
“…Computer-aided technology of deep learning (DL) may be helpful in screening for this subtype of PACD. We previously reported the good performance of DL of AS-OCT in detecting PIC in the same dataset 15. The AUC-ROC was 0.95 (95% CI=0.91 to 0.99), sensitivity was 87.9%, and specificity was 97.6%.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…GANs have also attracted a lot of interest in the medical field to generate synthetic data for various applications, such as data augmentation for patient data collected from Internet of Medical Things devices, as the process of data collection can run into trouble for various reasons and cause problems for patient monitoring, and ultimately for clinical decision-making systems [28]. GAN-based models have also been used for the fast MRI (magnetic resonance imaging) reconstruction of blurry scans [29], as well as the segmentation of meibomian glands from infrared images, i.e., automatically identifying the area of meibomian glands [30], and style transfer from UBM (Ultrasound Biomicroscopy) to AS-OCT (Anterior Segment Optical Coherence Tomography) in ophthalmology image domains [31]. VAE-GAN models further combine the architecture of both methods, i.e., they use a GAN-like architecture where the discriminator is a variational autoencoder [32].…”
Section: Introductionmentioning
confidence: 99%